Transverse myelitis associated with autoimmune polyglandular syndrome type 3B: A case report in Peru - Vences, Miguel A. (2023)
Autoimmune polyglandular syndrome is a rare disease with a low incidence worldwide. We present the case of an adult male with a history of parietal antibody-positive gastritis, central retinal vein obstruction and transverse myelitis. The patient was admitted for exacerbation of myelitis symptoms. The thyroid profile was positive for antibodies, indicating the presence of euthyroid autoimmune thyroid disease. The patient was finally diagnosed with autoimmune polyglandular syndrome type 3B. In the absence of adequate response to methylprednisolone and immunoglobulin, we started treatment with cyclophosphamide and later maintenance therapy with azathioprine. At one year of follow-up, the patient presented paraparesis as sequel, did not present new relapses and control tests were negative for another associated disease.